1998
DOI: 10.1002/(sici)1096-8628(19980328)81:2<134::aid-ajmg3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SCA1, DRPLA, MJD, SCA2, and SCA6 CAG repeats in 48 portuguese ataxia families

Abstract: The spinocerebellar ataxias (SCAs) are clinically and genetically a heterogeneous group of neurodegenerative disorders. To date, eight different loci causing SCA have been identified: SCA1, SCA2, Machado-Joseph disease (MJD)/SCA3, SCA4, SCA5, SCA6, SCA7, and dentatorubropallidoluysian atrophy (DRPLA). Expansion of a CAG repeat in the disease genes has been found in five of these disorders. To estimate the relative frequencies of the SCA1, DRPLA, MJD, SCA2, and SCA6 mutations among Portuguese ataxia patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…Compared with the averaged frequency of ADCA subtypes in other districts of Japan (Table 1) (Takano et al 1998;Sasaki et al 2003), the low frequency of SCA3/MJD is characteristic of Nagano. SCA3/MJD is the most prevalent ADCA subtype in Japan (Table 1) as well as in the majority of countries (Jardim et al 2001;Tang et al 2000;Stevanin et al 1997;van de Warrenburg et al 2002;Silveira et al 1998;Soong et al 2001). This is also the case in the Niigata (43%) and Nagoya (39%) districts, which are geographically adjacent to Nagano; therefore, the low frequency of SCA3/MJD in Nagano (3%) is noteworthy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with the averaged frequency of ADCA subtypes in other districts of Japan (Table 1) (Takano et al 1998;Sasaki et al 2003), the low frequency of SCA3/MJD is characteristic of Nagano. SCA3/MJD is the most prevalent ADCA subtype in Japan (Table 1) as well as in the majority of countries (Jardim et al 2001;Tang et al 2000;Stevanin et al 1997;van de Warrenburg et al 2002;Silveira et al 1998;Soong et al 2001). This is also the case in the Niigata (43%) and Nagoya (39%) districts, which are geographically adjacent to Nagano; therefore, the low frequency of SCA3/MJD in Nagano (3%) is noteworthy.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have indicated that SCA6, SCA3/MJD, and DRPLA are the most prevalent subtypes of ADCA in Japan despite a considerable variation in the frequency of each subtype among districts . The frequency of ADCA subtypes also varies among countries (Jardim et al 2001;Tang et al 2000;Stevanin et al 1997;van de Warrenburg et al 2002;Silveira et al 1998;Soong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, at least 29 of them have been mapped, and 15 genes have been identified. An exonic unstable CAG repeat expansion is the most frequent mutation associated with this group of neurodegenerative disorders 1 . Machado Joseph disease (MJD) or spinocerebellar ataxia type 3 (MJD/SCA3) seems to be the most common late-onset spinocerebellar ataxia in many world regions, including Germany, Brazil, Portugal, India, France, North America, Japan, China and Taiwan [1][2][3][4][5] .…”
Section: Machado Joseph Disease: Volumetric Analysismentioning
confidence: 99%
“…40 The relative frequencies of the different CAG repeat expansions have been determined by molecular typing in several populations. [41][42][43][44][45][46][47][48][49][50][51][52][53][54] However, most of the large series do not clearly indicate the ethnic and/or geographical origin of the families. Although in most countries SCA3/MJD is the major locus, the relative frequencies of SCAs vary widely according to the geographical origin.…”
Section: Frequency and Origin Of The Mutationsmentioning
confidence: 99%